2016
DOI: 10.1177/0959354316638181
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Freud and Kohut on narcissism

Abstract: Narcissism continues to be an important topic of research, with a great deal of ongoing empirical work in social and personality psychology. But there are theoretical issues that have received less attention recently, including those that relate to the foundational theories of the psychoanalytic tradition. As the first step in a larger project of reevaluation, this article offers a critical review of Freud and Heinz Kohut’s theories of narcissism. Centered on a theoretical reconstruction, it clarifies several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…He explains that he has taken actions throughout his life with the objects he has made and the images of the objects. Freud points out that recognizable mechanisms are in place to modify narcissistic drives beyond object-love object-cathexis, including repression, sublimation, and idealization (Cratsley, 2016). The better term to describe the instinctive drive is "need" (Freud, 2000: 86).…”
Section: The Consept Of Narcisism and Different Approaches: Sigmund F...mentioning
confidence: 99%
See 1 more Smart Citation
“…He explains that he has taken actions throughout his life with the objects he has made and the images of the objects. Freud points out that recognizable mechanisms are in place to modify narcissistic drives beyond object-love object-cathexis, including repression, sublimation, and idealization (Cratsley, 2016). The better term to describe the instinctive drive is "need" (Freud, 2000: 86).…”
Section: The Consept Of Narcisism and Different Approaches: Sigmund F...mentioning
confidence: 99%
“…In particular, Kohut argued that creativity, empathy, the ability to reflect on human impermanence, humor, and wisdom are linked to the developmental lines of narcissism. Narcissism is the "libidinal fuel" that enables the development of such traits (Cratsley, 2016). Kohut (1966) suggested that narcissism is not necessarily pathological but has an independent developmental sequence from infancy to adulthood.…”
Section: The Consept Of Narcisism and Different Approaches: Sigmund F...mentioning
confidence: 99%
“…He explains that he has taken actions throughout his life with the objects he has made and the images of the objects. Freud points out that recognizable mechanisms are in place to modify narcissistic drives beyond object-love object-cathexis, including repression, sublimation, and idealization (Cratsley, 2016). The better term to describe the instinctive drive is "need" (Freud, 2000: 86).…”
Section: The Consept Of Narcisism and Different Approaches: Sigmund F...mentioning
confidence: 99%
“…In particular, Kohut argued that creativity, empathy, the ability to reflect on human impermanence, humor, and wisdom are linked to the developmental lines of narcissism. Narcissism is the "libidinal fuel" that enables the development of such traits (Cratsley, 2016). Kohut (1966) suggested that narcissism is not necessarily pathological but has an independent developmental sequence from infancy to adulthood.…”
Section: The Consept Of Narcisism and Different Approaches: Sigmund F...mentioning
confidence: 99%
“…Kohut suggested that the narcissistic transferences, or selfobject transferences as he named them later on, testify to the presence of the narcissistic disorder and are, in fact, the key criterion for diagnosing the narcissistic personality disorder. He played down the relevance of theoretical knowledge and research data to the diagnosis of narcissism and likewise underestimated the significance of extratherapeutic symptoms and factors in this context (Basch, 1991;Cratsley, 2016;Galatzer-Levy, 1991;Kohut, 1984Kohut, / 2009b. Instead, Kohut relied essentially on data empathically gleaned from patients' accounts during treatment sessions-a practice consistent with his self psychology and its focus on the notion of empathy in psychoanalytic treatment as the ultimate tool for understanding the patient's inner world.…”
Section: Kohut's Diagnostic Model Primarily Based On Selfobject Trans...mentioning
confidence: 99%